Analysis Of Community Satisfaction Index On Public Services At Amen District Office Lebong District - Mahendry, Hendriek; Soleh , Ahamd; Abi , Yudi Irawan (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2023)
The purpose of this study was to determine the analysis of the community satisfaction index for public services at the Amen District Office, Lebong Regency.The sample in this study was 217 people from Amen District, Lebong Regency, who received services from the Amen District Office, Lebong Regency. The data collection uses a questionnaire and the analysis method used is to use the measurement of the Community Satisfaction Index (IKM) value based on the Regulation of the Minister of Administrative Reform and Bureaucratic Reform of the Republic of Indonesia Number 14 of 2017 concerning Guidelines for Compiling Public Satisfaction Surveys of Public Service Provider Units which are calculated using the value weighted average of each service element. The Community Satisfaction Index (IKM) score for the quality of public services at the Amen sub-district office, Lebong Regency is 79.20 with service quality B and the service unit performance assessment is "Good" because it is in the value interval of 76.61 - 88.30. This shows that the people who receive services from the Amen Sub-District Office, Lebong Regency, assess the services provided by the Amen Sub-District Office, Lebong Regency as good. The cost/tariff element gets the highest rating with an average score of 3.61 with the Very Good assessment criteria. This illustrates that the community views the Amen District Office of Lebong Regency as providing free services without being charged a fee. The lowest satisfaction score is 2.80 namely system, mechanism and procedure. This illustrates that the service procedures in the Amen sub-district office are not maximized because the processing of documents is still complicated, such as lacking requirements, the official signing the document is not in place.